Corrosivity Assessment of Hybrid Amine-Local Solvent Blends in Natural Gas Sweetening - Tare Caroline Gillow; Ipeghan J. Otaraku; Peter O. Muwarure; Johnson Nnadikwe (SEAN Institute, 2025)
This study optimised hybrid amine-local solvent blends for sustainable natural gas sweetening, tackling corrosion and environmental footprint of imported monoethanolamine (MEA). The study designed and evaluated an absorption process using blends of MEA with solvents derived from agricultural waste Plantain Peel Ash Extract (PPAE). The study integrates computational corrosion prediction models from the outset, acknowledged and addressed a common deficiency, performance optimisations were evaluated with critical material compatibility constraints from the beginning.Corrosivity assessment predicted a manageable corrosion rate of 0.29 mm/year for the optimal blend, within acceptable limits for carbon steel with standard inhibition. The study conclusively establishes the 50/50 MEA/PPAE hybrid solvent as a technically robust and environmentally superior alternative. It successfully valorises local agricultural waste, reduces dependency on imported chemicals, and aligns with Nigeria's local content policy and global sustainability goals, offering a viable pathway for greener and more cost-effective natural gas processing.